First trimester screening for pre‐eclampsia in Chinese pregnancies: case–control study. (11th January 2018) - Cheng, YKY; Leung, TY; Law, LW; Ting, YH; Law, KM; Sahota, DS
Abstract : Objective: To assess the potential of screening for pre‐eclampsia (PE) in a Chinese population. Design: Case–control study. Setting: Teaching hospital in Hong Kong. Population: A total of 3330 women having a viable singleton pregnancy attending first‐trimester Down‐syndrome screening. Methods: Mean arterial pressure (MAP), bilateral uterine artery pulsatility index (UtA‐PI), and placental growth factor (PlGF) were measured. Screening markers were transformed to multiples of the gestational median (MoM) and adjusted for maternal and pregnancy characteristics. MoM distributions in PE and non‐PE pregnancies were compared with published expected values. PE screening performance was assessed using area under receiver operating curves (AUROC). Main outcome measures: PE detection rate. Results: A total of 30 (0.9%) women developed either early (<34 weeks) or late (≥34 weeks) onset PE. MAP was dependent on maternal BMI, UtA‐PI on fetal crown rump length, uterine artery peak systolic velocity (UtA‐PSV) on maternal age and gestation, and PlGF on gestation in non‐PE pregnancies. MoM distributions determined using published Fetal Medicine Foundation models deviated significantly from one for both MAP ( P < 0.0001) and PI ( P < 0.0001), but not PlGF ( P = 0.52) in non‐PE pregnancies, whilst PlGF MoM distributions in those who developed early as opposed to late onset PE were significantly higher ( P = < 0.05). AUROC for any PE using multiple markers was 0.72 (95% CI: 0.64–0.81) with detection rates of 72 and 55% for early and late PE, respectively, for a 10% false positive rate. Conclusion: Detection rates for PE in our Chinese population were lower than the expected 90–95% even after adjusting MoM for local women's characteristics. Funding: General Research Fund (Project number 470513). Tweetable abstract: Pre‐eclampsia screening in the Chinese population had detection rates lower than previously published results. Tweetable abstract: Pre‐eclampsia screening in the Chinese population had detection rates lower than previously published results.